The registration of songs in the Infolk database - Benz, Nicola (Traditiones (Ljubljana), 2005)
The folk song archives in all of Austria's provinces are in charge of large collections of songs and melodies from a research period dating over one hundred years. To make these useable and accessible, a comprehensive archiving system and scholarly registration of the complete collections had to be created on the basis of musical-poetical figures, text- and music genres, functions, and occasions. The Virtual Network of Folk Songs Archives in Austria enables access to all the catalogues of the connected archives with their unique and specific regional collections, and established documentary evidence of the great variety of songs and melodies associated with Austria.
Keywords: etnomuzikologija; ljudske pesmi; Ethnopoetics; arhivsko gradivo; podatkovne baze; Austria; Avstrija